An integrated model of e-service quality and public satisfaction for smart city initiatives in the Abu Dhabi local government - Saeedmusallam Moqbil, Alrashdi Hamdan (2022)
The efficient management of resources against the background of urban developments has become critical to the development of sustainable cities. Several governments worldwide, including the UAE, are faced with an increasing challenge of urbanisation in social spaces. Resorting to smart cities to resolve urbanisation, the UAE, and the Abu Dhabi Emirate has made significant strides in this regard. Nonetheless, challenges remain pertinent, adoption is staggered, and overall service quality and the level of public satisfaction remain questionable. In this background, the study aims to investigate the impact of smart city initiatives on the government e-service quality and public satisfaction in Abu Dhabi Local Government. Particular reference is made to the e-service initiatives of TAMM and Jobs Abu Dhabi. Theoretically, the study builds on the Chourabi Model of Smart City Dimensions and the e-SERVQUAL model measurement of e-service quality. A quantitative research method was adopted, considering a sample of 384 users of the two selected smart service initiatives. Empirical findings were presented following the structural equation modelling analytical technique. Findings show that the smart city domain of institutional processes has a significant impact on e-service quality (B = 0.613, p < 0.05); however, the smart city technology (B = -0.021, p = n.s) and human capital (B = 0.019, p = n.s) do not improve e-service quality in the Abu Dhabi local government. Also, from the observations, trust did not qualify as a significant moderator of the impact of service quality on public satisfaction (R2 change = .0002, p = ns). Findings, however, supported that service quality differs across the various smart city domains (R2 change = .0149, p < 0.05). The study contributes to the existing body of knowledge by establishing that smart city dimensions partly have a significant influence on e-service quality, which in turn influences public satisfaction. The study also makes a novel contribution to knowledge by establishing the moderating effect of policy domains on the relationship between e-service quality and public satisfaction. It shows that the effect of e-service quality on public satisfaction vary based on the policy domain. The study recommended that Abu Dhabi Local Government improve public satisfaction and maximise the success of the Abu Dhabi Smart City Initiative.